Reimagining accessible architecture: Inclusive housing through a pluriversal approach - Barth, Thea Magnussen (My University, 2025)
How can a pluriversal approach to the transformation of existing housing foster accessibility, adaptability, and inclusivity for diverse users? Contemporary housing often overlooks the varied needs of accessibility, treating it as an afterthought rather than an integral aspect of design. This oversight results in environments that segregate and exclude individuals with disabilities, reinforcing social marginalisation. While investigating accessibility and exclusion in architecture, pluriversal design theory appeared applicable. The theory introduces seven design principles, which in this thesis have been used as the foundation for the process. However, to move from theory to architectural design, it became necessary to develop my own strategies in response to the specific site, context, and people involved. This thesis investigates how we can create homes that embrace diversity and explores how we can live in a world of multiple worlds, a pluriverse. The author does not believe that architects know best or that they alone should decide what is right for others. It is the diversity of people that forms a good architectural project. This belief shaped the participatory process at the core of the thesis. Interviews and workshops were conducted with a small group of people with varied needs, backgrounds, and challenges. Their insights informed the design and are represented through five fictional personas. These personas are used to develop narratives that reveal how space is experienced, both before and after transformation. The speculative design proposal reflects how a pluriversal approach, supported by participation, can shape more inclusive environments. The transformation of an existing housing development in Oslo serves as the test site. The project is not intended to provide universal answers, but to offer a way of working differently, one that values empathy, lived experience, and designing with, not for, others. It also points to the need for further reflection on whether current regulations can support more inclusive and plural ways of designing.
Keywords: Accessible architecture, Pluriversal design, Participatory design, Personas, Narratives